The impact of including carers in museum programmes for people with dementia: a realist review. Issue 1 (2nd January 2021) - Kinsey, Debbie; Lang, Iain; Orr, Noreen; Anderson, Rob; Parker, Daisy
ABSTRACT: Background : "In the moment" museum programmes for people with dementia (PwD) are an increasingly popular way of supporting people to live well. Most programmes include carers, though it is not well understood what effects, if any, their inclusion has. This review aimed to understand how including carers in museum programmes impacts the PwD, the carer, and the relationship between them. Methods : A realist review of peer-reviewed and grey literature was conducted to develop theory in answer to the research questions. Results : Twenty-three documents were included and 15 theory statements were developed within four themes: seeing the PwD in a new way, shared respite, excess disability, and reduced social isolation. Conclusions : As both positive and negative impacts were found, it is important to consider that programmes may not be beneficial for all dyads. The review offers recommendations to support positive outcomes for dyads, highlights gaps in the literature, and suggestions for further research.